2008
DOI: 10.1074/jbc.m801992200
|View full text |Cite
|
Sign up to set email alerts
|

Wild Type α-Synuclein Is Degraded by Chaperone-mediated Autophagy and Macroautophagy in Neuronal Cells

Abstract: ␣-Synuclein (ASYN) is crucial in Parkinson disease (PD)pathogenesis. Increased levels of wild type (WT) ASYN expression are sufficient to cause PD in humans. The manner of posttranscriptional regulation of ASYN levels is controversial. Previously, we had shown that WT ASYN can be degraded by chaperone-mediated autophagy (CMA) in isolated liver lysosomes. Whether this occurs in a cellular and, in particular, in a neuronal cell context is unclear. Using a mutant ASYN form that lacks the CMA recognition motif and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
584
1
21

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 625 publications
(626 citation statements)
references
References 42 publications
(54 reference statements)
20
584
1
21
Order By: Relevance
“…[170] identified in the alphaͲsyn sequence, the pentapeptide motif required to target cytosolic proteins to lysosomal degradation via chaperoneͲmediated autophagy (CMA). In cellular models and rodents, alphaͲsyn was shown to interact with lysosomeͲassociated membrane protein 2A (LAMPͲ2A), a transmembrane receptor of substrates for lysosomal degradation, giving evidence to the theory that CMA is involved in its clearance [170,174].Accordingly, LAMPͲ2A gene silencing slowed the degradation of monomeric and oligomeric species of alphaͲsyn in primary neurons of the ventral midbrain [174]. CMA, however, was not the only pathway for alphaͲsyn degradation.…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
See 1 more Smart Citation
“…[170] identified in the alphaͲsyn sequence, the pentapeptide motif required to target cytosolic proteins to lysosomal degradation via chaperoneͲmediated autophagy (CMA). In cellular models and rodents, alphaͲsyn was shown to interact with lysosomeͲassociated membrane protein 2A (LAMPͲ2A), a transmembrane receptor of substrates for lysosomal degradation, giving evidence to the theory that CMA is involved in its clearance [170,174].Accordingly, LAMPͲ2A gene silencing slowed the degradation of monomeric and oligomeric species of alphaͲsyn in primary neurons of the ventral midbrain [174]. CMA, however, was not the only pathway for alphaͲsyn degradation.…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…CMA, however, was not the only pathway for alphaͲsyn degradation. Vogiatzi et al (2008)[174]also reported that clearance of WT alphaͲsyn was in part mediated by macroautophagy. The study involved the selective macroautophagy inhibitor 3Ͳmethyladenine (3ͲMA), which led to a considerable increase of the steady state levels of alphaͲsyn in PC12 cells and in primary cortical and ventral midbrain neurons, suggesting that dysfunction of this degradation process could also contribute to the gradual accumulation of endogenous WT alphaͲsyn in sporadic PD.Furthermore, oxidative stresslinked to mitochondrial dysfunction may also increase misfolded proteins and therefore lead to aggregation of alphaͲsyn and subsequent death of dopaminergic neurons [175].…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…CMA, however, was not the only pathway for a-syn degradation. Vogiatzi et al [174] also reported that clearance of WT a-syn was in part mediated by macroautophagy. The study involved the selective macroautophagy inhibitor 3-"methyladenine, which led to a considerable increase in the steady-state levels of a-syn in PC12 cells and in primary cortical and ventral midbrain neurons, suggesting that dysfunction of this degradation process could also contribute to the gradual accumulation of endogenous WT a-syn in sporadic PD.…”
Section: Oxidative Stress In Familial Pdmentioning
confidence: 98%
“…Cuervo et al [170] identified, in the a-syn sequence, the pentapeptide motif required to target cytosolic proteins to lysosomal degradation via chaperone-mediated autophagy (CMA). In cellular models and rodents, a-syn was shown to interact with lysosome-associated membrane protein 2A (LAMP-2A), a transmembrane receptor of substrates for lysosomal degradation, giving evidence to the theory that CMA is involved in its clearance [170,174]. Accordingly, LAMP-2A gene silencing slowed the degradation of monomeric and oligomeric species of a-syn in primary neurons of the ventral midbrain [174].…”
Section: Oxidative Stress In Familial Pdmentioning
confidence: 99%
See 1 more Smart Citation